Decarboxylative-Mediated Regioselective 1,3-Dipolar Cycloaddition for Diversity-Oriented Synthesis of Structurally exo′-Selective Spiro[oxindole-pyrrolidine-dihydrocoumarin] Hybrids - Liu, Xiong-Wei; Chang, Shun-Qin; Wang, Qi-Lin; Chen, Shuang; Wang, Jun-Xin; Zhou, Wei; Zhou, Ying (Synthesis, 2020)
A general and practical three-component regioselective 1,3-dipolar cycloaddition of 3-amino-oxindole-based azomethine ylides and coumarins has been developed. This reaction displayed good substrate tolerance and gave a diverse array of biologically relevant spiro[ox-indole-pyrrolidine-dihydrocoumarin] derivatives bearing four contiguous stereocenters including one spiro quaternary center in moderate to high yields (up to 90%) with high diastereoselectivities (up to 15:1 dr). It is based on the application of carboxylic acid activated coumarins as dienophiles followed by a decarboxylation process. The possible mechanism of the 1,3-dipolar cycloaddition is proposed via an exo′-transition state. Furthermore, this is the first example of decarboxylative-mediated regioselective 1,3-dipolar cycloaddition of 3-amino-oxindole-based azomethine ylides and coumarins.
Keywords: decarboxylative; regioselective; 1,3-dipolar cycloaddition; diversity-oriented synthesis; multiple pharmacore molecules